SARS-CoV-2 seroprevalence among health care workers in a new york city hospital: A cross-sectional analysis during the COVID-19 pandemic (2020)
Background New York City (NYC) has endured the greatest burden of COVID-19 infections in the US. Health inequities in South Bronx predisposed this community to a greater number of infections cases, hospitalisations and mortality. Health Care Workers (HCWs) are at high-risk of exposure to the infection. This study aims to assess seroprevalence and associated characteristics of consenting HCWs from a NYC public hospital. Methods Cross sectional study including serum samples for qualitative SARS-CoV-2 antibody testing with nasopharyngeal swabs for SARS-CoV-2 PCR and completion of an online survey capturing demographics, COVID-19 symptoms during the preceding months on duty, details of healthcare and community exposure, and travel history were collected from consenting participants in May 2020. Participants’ risk of exposure to COVID-19 infection in hospital and in the community was defined based on CDC guidelines. Travel history to high-risk areas was also considered an additional risk. The Odds Ratio with bivariable and multivariable logistic regression was used to assess characteristics associated with seroprevalence. Results A total of 500 HCW were tested, 137 (27%) tested positive for SARS-CoV-2 antibody. Symptomatic participants had a 75% (98/130) rate of seroconversion compared to those without symptoms. Subjects with anosmia and ageusia had increased odds of seroconversion in comparison to those without these symptoms. Community exposure was 34% (44/130) among those who had positive antibodies. Conclusion Seroprevalence among HCWs was high compared to the community at the epicenter of the pandemic. Further studies to evaluate sustained adaptive immunity in this high-risk group will guide our response to a future surge.